An Integrated Analysis of Prognostic Signature and Immune Microenvironment in Tongue Squamous Cell Carcinoma - Jin, Yi; Wang, Zhanwang; Tang, Weizhi; Liao, Muxing; Wu, Xiangwei; Wang, Hui (Frontiers in Oncology, 2022)
Tongue squamous cell carcinoma (TSCC), one of the most frequent cancers of the oral cavity, owns unsatisfactory survival even combining treatments involving surgery, radiationand chemotherapy. Immune checkpoints inhibitors could prolong survival time especially the patients with recurrent or metastatic stage. However, there are rare effective biomarkers to predict prognosis and guide immunotherapy. Firstly, we utilized the WGCNA analysis to identify the co-expression module and selected the turquoise module for next investigation. The GO and KEGG analysis were used to visual the innate pathways, indicating that the pathways of cell junction organization, response to topologically incorrect protein and regulation of cell adhesion may play an essential role. Then we select eleven crucial predictive genes (PLXNB1, N4BP3, KDELR2, INTS8, PLAU, PPFIBP2, OAF, LMF1, IL34, ZFP3, MAP7D3) and established a risk model based on these genes by performing Cox and Lasso analysis in TCGA and GSE65858 databases with overall survival. KM analysis and ROC curve suggested that the risk model had a better prognostic effectiveness than other clinical traits. Subsequently, we applied the Consensus Clustering to classify the TSCC samples into two groups with sharply different survival. The ESTIMATE and CIBERSORT were used to display the immune landscape of TSCC, which indicating that stromal score and types of immune cells including B cell naïve, plasma cells, T cells CD8, T cells CD4 memory resting, T cells CD4 memory activated, T cells follicular helper and T cells regulatory (Tregs) may mediate the heterogeneous immune microenvironment. To further identify the hub genes, we downloaded GEO datasets (GSE41613 and GSE31056) and successfully validated the risk model. Finally, two hub genes (PLAU and PPFIBP2) were identified and re-verified to be intimately associated with CD4+, CD8+ T cells and PD1/PD-L1.